Current Cash Equivalent, Additivity, and Financial Action. - Larson, Kermit; Schattke, R. W. (The Accounting Review, 1966)
The article criticizes a work of R. J. Chambers that provides an outstanding and provocative contribution to the development of accounting theory. The criticism involves a brief review of the relevant parts of Chambers' system, a technical discussion of the requirement of additivity in measurement, a discussion of whether Chambers' chosen property fits this technical requirement, and a more general discussion of the implications of the criticism. The authors conclude, for two reasons, that current cash equivalent is a nonadditive property. First, it is nonadditive because summation of the realizable prices of individual assets presumes independent sales of those assets and therefore does not involve a mode of combination. Second, it allows the independent sale of assets as a mode of combination and proceeds to question its possible artificiality